Belief in Bambarayon (Paddy Spirits) among the Kadazandusun of North Borneo - Low, Kok On (University of Malaya, 2012)
Rice is the staple food of the Kadazandusun community residing on the west coast of North Borneo (Sabah, Malaysia). Crop yields are of the utmost importance to the Kadazandusun farmers, and it is not surprising that great religious significance is attached to all aspects of rice cultivation. Belief in the paddy spirits, Bambarayon (variously pronounced by the different Kadazandusun subgroups), is witnessed in the myths and legends of the various Kadazandusun subgroups. Bambarayonis considered to be present in every grain of paddy and is the focus of the many ceremonies, charms,and taboos associated with paddy farming. Based on previous research findings and raw data gathered from the field trips, this paper represents an extensive study of the beliefs surrounding Bambarayon. As well as focusing on the origins of the paddy spirits and their classification, the paper examines related ritual ceremonies and charms and briefly compares the findings with those from traditional belief systems elsewhere in Malaysia and across Southeast Asia. In so doing, the author hopes to facilitate a better understanding of one of the Kadazandusun’s central beliefs.